2020
DOI: 10.1051/e3sconf/202020205021
|View full text |Cite
|
Sign up to set email alerts
|

Mercury (Hg) concentration of river water and sediment in Tambang Sawah village due to gold mining without permission

Abstract: The rise of mining activities without permission (PETI) which was a people’s mining from Dutch colonial legacy, located in the Tambang Sawah Village, Pinang Belapis District, Lebong Regency has caused environmental problems especially mercury pollution in that village river water. The sampling method refer to Japan Public Health Association (JPHA), then sample analyzed in the national standard laboratory and the results were compared with the Government Regulation of Republic Indonesia No. 82 of 2001 on Manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Heavy metal mercury is easily soluble and changes the stability of the carbonate form to hydroxide, which forms particulate bonds in the waters. Then precipitation occurs and ends in the formation of mud [19][20]. Mercury metal is not easily detected.…”
Section: Results and Discussion Mercury Accumulation In Water And Sed...mentioning
confidence: 99%
“…Heavy metal mercury is easily soluble and changes the stability of the carbonate form to hydroxide, which forms particulate bonds in the waters. Then precipitation occurs and ends in the formation of mud [19][20]. Mercury metal is not easily detected.…”
Section: Results and Discussion Mercury Accumulation In Water And Sed...mentioning
confidence: 99%
“…What are the real effects of illegal mining on the environment and public health? To answer this question, we added quantitative data for our sample sites, drawn from the results of secondary-source studies undertaken in the past ten years at several gold-mining sites in Indonesia [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. The environmental impacts and health threats from illegal mining operations can be seen in Figure 7 .…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the latter, the effects of illegal gold mining have the potential to cause environmental damage in the long term, taking the form of negative changes to the landscape, landslides, and erosion, as well as water pollution in/around mining sites. A number of studies have reported upon the contribution of ASGM to land degradation [ 19 , 42 , 75 ], river water pollution [ 18 , 74 , 76 , 77 ], and soil/sediment pollution [ 18 , 25 , 26 , 36 , 57 , 78 ], whose conditions do not meet established quality standards. Indonesia Government Regulation 82/2001 for mercury in river water is 0.002 mg/L and in drinking water or in the water supply it is 0.001 mg/L.…”
Section: Impact Of Asgm Activitiesmentioning
confidence: 99%